The Impact of Improper Body Posture on Office Workers’ Health - Al-Nakhli, Hani H.; Bakheet, Hussein G. (International Journal of Innovative Research in Medical Science, 2020)
Recent data has shown increasing rates of musculoskeletal disorders among the working community. These health-related complications are considered to be amongst the leading causes of disability, and limitation of motion within modern office workers. Many of these disorders are commonly caused by improperly accommodated workplaces. The importance of this study surfaces around the challenges that will be faced during the implementation of Saudi vision’s 2030; if this topic is not addressed adequately. The study aims to detect and prevent office related injuries by investigating their associations with improper workstation ergonomics. This was conducted within the framework of studying the current situation of office ergonomics with focus on sitting postures. Correlations between workers’ musculoskeletal pains, and their habits were evaluated. For collecting the necessary data, a thirty-item questionnaire was distributed to more than one thousand randomly selected workers within Saudi Arabia. This questionnaire was developed to better study the personal demographics, medical information, muscular pain, physical therapy history, workstation ergonomics, and sitting practices. After filtering and analyzing the collected data, the results of the survey indicated that 78% of the total participants had experienced some sort of musculoskeletal pains, from which 84% of them stated that their sitting postures are awkward, during their working hours. Also, from the total number of musculoskeletal pain sufferers, approximately 32% visited a physical therapy clinic seeking relief for their pains. However, only 39% of them benefitted from the physical therapy interventions, whereas 61% did not. From the individuals whom did not respond to physical therapy, 80% of them identified that they were equipped with ergonomically inconvenient workstations or they were not aware of the correct way to occupy their workstations. To a greater extent, 74% of the total number of participants were supplied with ergonomically inconvenient workstations, which suggests that the employment of anthropometry and workstation ergonomics is not up to standards in Saudi Arabia, causing an extensive impact in escalating muscular pain. In conclusion, raising the awareness of the population regarding the importance of workplace ergonomics is critical; after highlighting the risks of awkward sitting postures. It is worth mentioning that the appropriate employment of office ergonomics requires the cooperation of both; employees and employers. Only by this alliance, ergonomics will contribute in increasing productivity, and decreasing time loss leading to the maintenance of healthy individuals.